HUBUNGAN PERSEPSI ORANGTUA DENGAN KELENGKAPAN IMUNISASI DASAR PADA BATITA USIA 1-3 TAHUN DI POSYANDU APEL - Oryza Intan Suri; Lely Ariantinah (STIKes IMC Bintaro, 2021)
Introduction: Basic immunization is the immunization given to every infant (age 0-11 months) which is compulsory consisting of 1 dose of Hepatitis B 0, 1 dose of BCG, 3 doses of DPT-HB-Hib, 4 doses of polio drops, and 1 dose of measles / MR (Indonesian Ministry of Health, 2018). In 2018, the complete basic immunization in Kelurahan Sawangan had not yet reached the target, namely 81.5% who had received complete basic immunization, where the target was 95%. Research Objectives: To determine the relationship between parental perceptions and completeness of basic immunization in toddlers 1-3 years old. Research Methodology: This study is an analytic observational study using a case-control design. The sample in this study were parents who have toddlers 1-3 years old at the Apel Rw 011 Cinangka Sawangan Depok, totaling 76 respondents using quota sampling technique. Collection techniques were obtained from questionnaires and KMS. Results: The univariate statistical test of 76 respondents 20-35 years old was 62 (81.6%), of the 76 respondents with tertiary education as many as 63 (82.9%), out of 76 respondents with an economic level of income of the UMR (98.7%) of respondents. The bivariate statistical test using the Chi-Square test obtained p < 0.05 (p = 0.001), indicating a significant relationship between parental perceptions and completeness of basic immunization. Conclusion: There is a significant relationship between parental perceptions and completeness of basic immunization for toddlers 1-3 years old.